2019
DOI: 10.1017/jfm.2019.610
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear behaviour of convergent Richtmyer–Meshkov instability

Abstract: A novel shock tube is designed to investigate the nonlinear feature of convergent Richtmyer–Meshkov instability on a single-mode interface formed by a soap film technique. The shock tube employs a concave–oblique–convex wall profile which first transforms a planar shock into a cylindrical arc, then gradually strengthens the cylindrical shock along the oblique wall, and finally converts it back into a planar one. Therefore, the new facility can realize analysis on compressibility and nonlinearity of convergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…It is found that at early stages the growth of the third harmonic in divergent geometry is much smaller than that in a planar or convergent geometry (Luo et al. 2019), which provides a further demonstration of weak nonlinearity. Although nonlinearity increases at late stages, the positive growth of the third harmonic approximately counteracts its negative feedback to the basic mode, which suggests a negligible influence of nonlinearity on the growth of overall perturbation amplitude.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It is found that at early stages the growth of the third harmonic in divergent geometry is much smaller than that in a planar or convergent geometry (Luo et al. 2019), which provides a further demonstration of weak nonlinearity. Although nonlinearity increases at late stages, the positive growth of the third harmonic approximately counteracts its negative feedback to the basic mode, which suggests a negligible influence of nonlinearity on the growth of overall perturbation amplitude.…”
Section: Resultsmentioning
confidence: 92%
“…2015; Luo et al. 2019). The growth of the third harmonic together with its feedback to the primary mode, predicted by the nonlinear model of Wang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental investigations of cylindrical converging RMI in shock tubes had been conducted by several researchers, such as Hosseini & Takayama (2005), Biamino et al (2015), Luo et al (2015Luo et al ( , 2018Luo et al ( , 2019a, Zhai et al (2017), Rodriguez et al (2017), Ding et al (2017Ding et al ( , 2019, Lei et al (2017), Li et al (2020), Vandenboomgaerde et al (2018, Courtiaud et al (2019), Sun et al (2020b) and Zou et al (2019). These experimental results are particularly helpful for the development of theory and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Hill, Pantano & Pullin 2006;Li et al 2019) and converging geometries (e.g. Lombardini & Pullin 2009;Luo et al 2019).…”
Section: Discussionmentioning
confidence: 99%